Exonuclease III-regulated target cyclic amplification-based single nucleotide polymorphism detection using ultrathin ternary chalcogenide nanosheets - Hu, Yanling (2020)
Herein, we report that the ternary chalcogenide nanosheet exhibits different affinity toward oligonucleotides with different lengths and efficiently quenches the fluorescence of dye-labeled DNA probes. Based on these findings, as a proof-of-concept application, the ternary chalcogenide nanosheet is used as a target cyclic amplification biosensor, showing high specificity in discriminating single-base mismatch. This simple strategy is fast and sensitive for the single nucleotide polymorphism detection. Ultralow detection limit of unlabeled target (250 fM) and high discrimination ratio (5%) in the mixture of perfect match (mutant-type) and single-base mismatch (wild-type) target are achieved. This sensing method is extensively compatible for the single nucleotide polymorphism detection in clinical samples, making it a promising tool for the mutation-based clinical diagnostic and genomic research.